Can the Marketing Authorisation Holder system improve the ESG performance of pharmaceutical manufacturers? - Li, Jiajing (Frontiers in Public Health, 2025)
IntroductionThe Marketing Authorisation Holder (MAH) system is an advanced drug registration mechanism widely adopted globally Nevertheless, there is a scarcity of in-depth empirical investigations concerning MAH within the context of pharmaceutical manufacturing enterprises.MethodsThis research endeavors to investigate the influence of MAH on the environmental, social and corporate governance (ESG) performance of companies through the application of the difference-in-differences model, leveraging firm data from China’s A-share-listed pharmaceutical manufacturing sector spanning from 2012 to 2019.ResultsFirst, MAH markedly enhances the ESG performance of pharmaceutical manufacturing entities. Secondly, MAH impacts firms’ ESG performance via three pathways, namely, boosting research and development (R & D) investment, diminishing the internal pay disparity, and lowering supply chain concentration. Thirdly, the effect of MAH on firms’ ESG performance is more pronounced in non-state-owned firms, those with elevated management shareholding, and firms with enhanced internal control levels. Furthermore, this study ascertained that MAH exerted no influence on firm ESG variance and real earnings management.DiscussionThe results offer actionable policy recommendations for refining the MAH system and promoting the sustainable development of pharmaceutical manufacturing firms. This study not only expands the research boundary of the economic consequences of the MAH system, but also affirms the key role of institutional innovation in the sustainable development of enterprises.